2021
DOI: 10.1016/j.jtocrr.2021.100143
|View full text |Cite
|
Sign up to set email alerts
|

The Survival Advantage of Lobectomy over Wedge Resection Lessens as Health-Related Life Expectancy Decreases

Abstract: Introduction Patients with early-stage NSCLC typically must choose between a surgery with superior local control (lobectomy) or one that preserves lung parenchyma (wedge). Recognizing that many patients with cancer have competing mortality risks unrelated to cancer, we investigated whether an established model of predicting life expectancy could be used to identify patients with stage I NSCLC for whom survival after wedge is not different from lobectomy. Methods A retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…These studies mostly involved open thoracotomy. The welldocumented (29) decrease in perioperative complications with VATS lobectomy in general is also noted in older patients: S3-2) (12,13,18,19,26,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). The hazard ratios (HRs) for OS and LCSS fairly consistently favor lobectomy.…”
Section: Mortality and Morbiditymentioning
confidence: 83%
See 1 more Smart Citation
“…These studies mostly involved open thoracotomy. The welldocumented (29) decrease in perioperative complications with VATS lobectomy in general is also noted in older patients: S3-2) (12,13,18,19,26,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). The hazard ratios (HRs) for OS and LCSS fairly consistently favor lobectomy.…”
Section: Mortality and Morbiditymentioning
confidence: 83%
“…Few adjusted NRCs address resection extent in compromised patients (Table S3-3) (38,104). Salazar et al analyzed patients with a life expectancy of ≤5 years (based on non-cancer characteristics; 67% age ≥80, 84% Elixhauser comorbidity ≥3) (38). Wedge (vs. lobectomy) was associated with worse LCSS, but fewer non-cancer deaths (90-day mortality excluded).…”
Section: Survival and Recurrencementioning
confidence: 99%
“…This could expand the pool of patients who can potentially benefit from surgical intervention. Studies have suggested that patients undergoing less extensive lung resections tend to have better postoperative outcomes, including reduced rates of complications and improved overall survival [ 21 ]. The decision to perform a specific type of surgery should be individualized on the basis of the patient’s overall health, tumor characteristics, and response to preoperative chemo-IO.…”
Section: Podcast Transcriptmentioning
confidence: 99%
“…We have recently shown that the benefit of a lobectomy over a wedge resection diminishes considerably among patients with shorter life expectancy due to age and comorbidities. 28 The decision for adjuvant chemotherapy may be heavily influenced by their potential to survive long enough to derive a benefit from additional therapy. In addition, it is critical to understand the goals of care for each individual patient and not assume that all patients who might obtain a small theoretical survival benefit are willing to undergo adjuvant treatments.…”
Section: Important Notes Related To Adjuvant Therapy Changes In the Staging Systemmentioning
confidence: 99%